Analisis Penyelesaian Komplain di Instalasi Gawat Darurat Instalasi RSUD. Dr. H. Abdul Moeloek Provinsi Lampung Tahun 2022 - Yuanita, Desy; Sary, Lolita; Muhani, Nova (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2024)
Background : The entire complaint data that has been handled at the Hospital. Dr. H. Abdul Moeloek Lampung Province, including data on nursing services totaling 73 (24%), medical services totaling 77 (25%), administrative services totaling 48%, facilities & infrastructure totaling 48 (16%), cleaning services and security services totaling 31(10) %). Methode:Type of qualitative research with a case study approach, measured using in-depth interviews, direct observation with 2 main informants (head of IGD), 2 key informants (Head of Planning and Head of Subdivision of PPPIP), and 3 triangulation of sources. Result: There are 6 principles of effective complaint handling according to ISO BS 10002 that have been going well, namely visibility in the implementation of complaint handling that has been running effectively and optimally. accessibility works effectively with easy access and information is spread in strategic places and is available in various facilities provided, Responsiveness is an explanation that is accurate in providing solutions to problems felt by patients for complaints with direct methods to officers. Accountability, Cost and continuous improvement in the application of the principles of complaint handling have been running effectively. 3 principles that have not been implemented effectively and need to be optimized in handling complaints including the application of objectivity, confidentiality in customer management, this is due to the spread of customer identity in the customer complaint group. Conclution: the members of the complaint handling team have complaint handling certificates, excellent service and must contain people who have no interest whatsoever/neutral and can be obtained from the hospital staff, develop a computer-based complaint management information system to make it easier to get information, handle and report complaints confidentiality can be maintained, customer service training/skills and optimizing the performance of the customer service team, creating a complaint service center and creating a suggestion box which is followed up and resolved based on agreed targets. Keyword: Analysis, Complain, Hospital